Regime or revolution? the dilemma of Syria’s religious institutions: the example of the Fatih Institute - Bakour Mohamad, Bachar (Taylor and Francis Ltd., 2020)
The Sunni ‘ulama of Syria did not respond to the 2011 revolution in a unified fashion. Whereas top scholars gave full support to initial protests, others aligned themselves with the regime. Quietism was the preferred choice of a third group. Taking the Fatih Institute as a case study, this paper presents the differing positions of the Faith scholars with their pronounced rationales. Adopting textual and contextual analysis, the paper examines these views on the basis of Islamic sources on one hand and the realistic situation of the Syrian prolonged crisis on the other hand. The paper concludes that the Syrian regime was able to exploit religious institutions to propagate its narrative of events. Also, co-opted scholars widely vary in their acquiescence and response to the regime’s demand. More impotently, with the absence of the essentially geo-political, and social considerations, the pro-revolution camp failed to consider the present vs. the expected harm, which resulted in massive bloodshed and major upheaval in the Syrian society as a whole.